The Power of Penitence: Penitent Women and the Friars in Medieval Florence - Lawless, Catherine (Cork University Press, 2024)
In this essay I propose to investigate the world of female mendicant piety through some of the imagery produced in mendicant churches or that which can be reliably connected to mendicant piety and to women, either in the iconography of represented women, or with women as its intended recipient. Firstly, however, I shall outline the marginality of female sanctity in large-scale representations in the two main mendicant churches of Florence, the Dominican Santa Maria Novella and the Franciscan Santa Croce. To provide a contrast to this large-scale work, my discussion shall then move to small-scale images, often allocated to the realms of ‘personal’, ‘private’ or ‘domestic’ devotion. I suggest that there were further spaces where these images functioned: that of the dwellings of the lay penitent women who clustered around the mendicant churches, either in groups or alone, dependent on them for the administration of the sacraments and for spiritual instruction.
Mendicants on the Margins
PUBLISHED
Cork
Keywords: Identities in Transformation; Making Ireland; Manuscript, Book and Print Cultures; Family, Church history; History of Gender and Sexuality; Medieval Europe; Religious History